The microarchitecture of DNA replication domains - Philimonenko, Anatoly A; Hodný, Zdenek; Jackson, Dean A; Hozák, Pavel (Histochemistry and cell biology, 2006)
Most DNA synthesis in HeLa cell nucleus is concentrated in discrete foci. These synthetic sites can be identified by electron microscopy after allowing permeabilized cells to elongate nascent DNA in the presence of biotin-dUTP. Biotin incorporated into nascent DNA can be then immunolabeled with gold particles. Two types of DNA synthetic sites/replication factories can be distinguished at ultrastructural level: (1) electron-dense structures--replication bodies (RB), and (2) focal replication sites with no distinct underlying structure--replication foci (RF). The protein composition of these synthetic sites was studied using double immunogold labeling. We have found that both structures contain (a) proteins involved in DNA replication (DNA polymerase alpha, PCNA), (b) regulators of the cell cycle (cyclin A, cdk2), and (c) RNA processing components like Sm and SS-B/La auto antigens, p80-coilin, hnRNPs A1 and C1/C2. However, at least four regulatory and structural proteins (Cdk1, cyclin B1, PML and lamin B1) differ in their presence in RB and RF. Moreover, in contrast to RF, RB have structural organization. For example, while DNA polymerase alpha, PCNA and hnRNP A1 were diffusely spread throughout RB, hnRNP C1/C2 was found only at the very outside. Surprisingly, RB contained only small amounts of DNA. In conclusion, synthetic sites of both types contain similar but not the same sets of proteins. RB, however, have more developed microarchitecture, apparently with specific functional zones. This data suggest possible differences in genome regions replicated by these two types of replication factories.
Keywords: proteinkinasa CDC2; Cyclin B1; buněčné jádro; lamin typ B; cyklin B; cyklin B1; Lamin Type B; DNA; DNA Replication; imunohistochemie; replikace DNA; DNA Polymerase I; monoklonální protilátky; HeLa Cells; Tissue Embedding; Antibodies, Monoclonal; zalévání tkání; Cell Cycle Proteins; RNA; Immunohistochemistry; Cell Nucleus; proteiny buněčného cyklu; DNA-polymerasa I; Humans; Microscopy, Immunoelectron; Cyclin B; imunoelektronová mikroskopie; CDC2 Protein Kinase; HeLa buňky; lidé